2005
DOI: 10.1159/000086668
|View full text |Cite
|
Sign up to set email alerts
|

Acebutolol-Induced Subacute Cutaneous Lupus Erythematosus

Abstract: Beta-blocking medications are rarely associated with drug-induced lupus erythematosus syndrome and have never been incriminated as a cause of subacute lupus erythematosus (SCLE). We present herein the first case of SCLE induced by acebutolol. A 57-year-old woman presented with a 1-month history of a cutaneous eruption of the photoexposed areas. One month ago, the patient had started a treatment with oral acebutolol to cure a hypertension of 1-year evolution. Physical examination revealed erythematous scaly ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 63 publications
1
12
0
1
Order By: Relevance
“…[5] The ANA pattern in our case was similar to a number of other cases, with antibodies to Ro and La Antigens being present in 50-71% of patients with SCLE. [67] Anti-DNA was not elevated as with other studies which have found it to be elevated in systemic lupus erythematosus but not in SCLE. [678] As with other studies, complement and ANCA were normal as was cardiolipin although it may be elevated in 16% of patients with SCLE.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…[5] The ANA pattern in our case was similar to a number of other cases, with antibodies to Ro and La Antigens being present in 50-71% of patients with SCLE. [67] Anti-DNA was not elevated as with other studies which have found it to be elevated in systemic lupus erythematosus but not in SCLE. [678] As with other studies, complement and ANCA were normal as was cardiolipin although it may be elevated in 16% of patients with SCLE.…”
Section: Discussionsupporting
confidence: 58%
“…[678] As with other studies, complement and ANCA were normal as was cardiolipin although it may be elevated in 16% of patients with SCLE. [4578] A transient depression of complement levels has also been reported. [4]…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The median incubation time was 6 weeks. The mean and median overall time 30 3 cases Nitrendipine 31 1 case Diuretics Hydrochorothiazide 3,10,22 10 cases Hydrochlorothiazide + triamterene 6 3 cases Chlorthiazide 5 2 cases Beta blockers Oxprenolol 32 4 cases Acebutolol 33 1 case Angiotensin-converting enzyme inhibitors Enalapril 10 2 cases Lisnopril 10 1 case Captopril 34 1 case Cilazapril 34 1 case Antifungals 30 of 117 reported cases: 25AE6% Terbinafine 12,14-16, [35][36][37] 29 cases Griseofulvin 13 1 case Chemotherapeutics 10 of 117 reported cases: 8AE5% Docetaxel 38 3 cases Paclitaxel 24, 38 3 cases Tamoxifen 39 2 cases Capecitabine 40, 41 2 cases Antihistamines 9 of 117 reported cases: 7AE7% Ranitidine 42 7 cases Brompheniramine 42 1 case Cinnarizine + thiethylperazine 43 1 case Immunomodulators 8 of 117 reported cases: 6AE8% Leflunomide 9,17,25, 44 5 cases Interferon a and b 10, 45 3 cases Antiepileptics 3 of 117 reported cases: 2AE6% Carbamazepine 46, 47 2 cases Phenytoin 48 1 case Statins 3 of 117 reported cases: 2AE6% Simvastatin 10, 49 2 cases Pravastatin 10 1 case Biologics 2 of 117 reported cases: 1AE7% Etanercept 50 1 case Efalizumab 51 1 case Proton pump inhibitors 2 of 117 reported cases: 1AE7% Lansoprazole 52 2 cases Nonsteroidal anti-inflammatory drugs 2 of 117 reported cases: 1AE7% Naproxen 53 1 case Piroxicam 26 1 case Hormone-altering drugs 2 of 117 reported cases: 1AE7% Leuprorelin 19 1 case Anastrozole 18 1 case Ultraviolet therapy 2 of 117 reported cases: 1AE7% PUVA 54 1 case PUVA and UVB 20 1 case Others 4 of 117 reported cases: 3AE4% Bupropion…”
Section: Resultsmentioning
confidence: 99%
“…ACE inhibitors have a long track record of safety and efficacy and have been studied in patients with lupus nephritis and severe hypertension, where they were shown to improve renal function in 64% of the patients although also improving BP control. 84 The β-blockers may precipitate or worsen Raynaud’s phenomenon 85 and can rarely cause drug-induced lupus 86,87 so they are used as second-line agents.…”
Section: Prevention and Treatmentmentioning
confidence: 99%